Inovasi Strategi Guru dalam Pembelajaran Terhadap Peningkatan Aktivitas Belajar Siswa - Gawise Gawise; Andi Lely Nurmaya G; Nur Dahniar; Irsan Irsan; La Safrin (Departement of Mathematics Education, 2023)
Learning strategies are methods that will be chosen and used by a teacher to convey learning material that aims to make it easier for students to receive and understand learning material. The effectiveness of student activity in the learning process is still low due to the lack of innovative strategies applied by the teacher in the learning process. These problems have an impact on achievement. The purpose of this research is to identify the teacher's strategy in learning the learning activities of students. The strategy carried out by the teacher in the learning process used by the teacher's activities is in the very good category with an average percentage of 90%. Not only is the teacher very good but student activity is in the very good category with an average percentage of 85%.